Divestiture strategy, CEO power and firm performance - Rayenda, Khresna Brahmana; You, Hui Wei; Yong, Xhin Rong (Emerald Publishing Limited, 2020)
Purpose–This study aims to examine the moderating role of chief executive officer (CEO) power on therelationship between divestiture strategy andfirm performance by framing the relationship under the agencyand power circulation theories.Design/methodology/approach–This study focuses on a sample of 319 non-financial public-listedcompanies in Malaysia from the year 2012–2016 and estimates the model under two-step generalized methodof moments panel regression to eliminate the endogeneity issue.Findings–The results show that divestiture strategy decreased thefirm performance. Meanwhile, greaterCEO power changed that divestiture effect but still failed to increase the performance. This study alsoindicates the CEO power strengthens the relationship betweenfirm performance and divestiture.Research limitations/implications–The overallfindings show that the positive moderating role ofCEO power on the relationship between divestiture and performance. This research confirmed the agency andpower circulation theories by showing that CEO power can make divestiture strategy works. However, themoderating plot tells different. CEO power may strengthen the relationship between divestiture andperformance; it fails to boost up the performance in overall. Therefore, this study is about CEO power on thestrategic decision and gives a good implication for corporate governance concerning the impact of CEO poweron the organization’s alignment process.Originality/value–This study examines the effect of CEO power on the performance of divestiturestrategy implementation by contesting the agency and power circulation theories within an emerging countrycontext.